Pengaruh Struktur Modal Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Desty, Rahel Mey (UNIB Press, 2024)
This study aims to determine the influence of capital structure and company growth on the value of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2017-2019 period. This research method uses quantitative methods. The sample in this study is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange for the 2017-2019 period. Sample selection was done by using purposive sampling method. The amount of data that was processed in this study was 42 data. The data analysis technique used in this study is panel data regression analysis with the help of the eviews 10 application. The results of this study indicate that capital structure has no effect on firm value while firm growth has a significant negative effect on the value of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Keyword: Company Value; Company Growth; Capital Structure